Pro WCF 4 practical Microsoft SOA Implementation - Pathak, Nishith (Apress, 2011)
Pro WCF 4.0: Practical Microsoft SOA Implementation is a complete guide to Windows Communication Foundation from the service-oriented architecture (SOA) perspective, showing you why WCF is important to service-oriented architecture and development. This book provides deep insight into the functionality of WCF, which shipped with .NET 4.0-like service discovery, routing service, simplified configuration, and other advanced features. Included in this title are informative examples that will aid the reader in understanding and implementing these important additions. This book also covers the unified programming model, reliable messaging, security, and the peer-to-peer programming model. You'll also learn how to move your current .NET remoting and web service applications to WCF, and how to integrate those applications with WCF 4. This book offers genuine insight into solving real enterprise problems using WCF and .NET 4.0